Explorations in philosophy - Mohanty, J. N. (Oxford University Press, 2001)
This collection contains essays by one of the leading philosophers of our times, J.N. Mohanty. Written in the 1990s, these essays provide insights into Indian philosophy and Mohanty's work spanning three decades. Mohanty's analysis of Indian philosophy dispels the characterization of Indian philosophy as simply a search for the spirit, showing that it is also a critical analysis of the data provided by experience.